From Adoption to Capability: Rethinking HR Analytics in Organizations: An Integrative Review of Applications, Outcomes, and Constraints - Chres Fransisco Patris Laoh; Daniel Peterson Silaban (Research Trend in Technology and Management, 2025)
Organizations are rapidly adopting HR analytics to support data-driven decision making. Yet much of the existing literature treats the use of analytics tools as evidence of organizational capability, leaving the distinction between adoption and capability largely unexamined. This study addresses this limitation by mapping the intellectual structure of HR analytics research through an adoption-to-capability perspective. Using a systematic integrative literature review of 138 peer-reviewed articles published between 2020 and 2026, we examine how HR analytics is applied across HR functions, which outcomes are reported, and which barriers persist across organizational contexts. The findings show that HR analytics research is concentrated on operational and managerial applications, particularly recruitment, retention, and performance management, and is mainly supported by descriptive and limited predictive analytics. Reported outcomes emphasize efficiency, performance improvement, and decision quality, while strategic contributions remain weakly evidenced. Persistent challenges related to skills, data infrastructure, governance, and conceptual fragmentation continue to constrain deeper capability development. Overall, the literature reflects early to intermediate stages of HR analytics capability maturity.